THE LANGUAGES WE SPEAK AFFECT OUR PERCEPTIONS OF THE WORLD - O.Yu. Mykhailyuk; H.Ya. Pohlod (Vasyl Stefanyk Precarpathian National University, 2015)
The article presents review of studies on interaction between language and thought and the way it influences our understanding of the world. This is an interesting and important new direction for the research on language and thought, as our society becomes increasingly global and has an increased need for clear communication across languages and cultures. With a better understanding of how language and thought interact to influence how we understand and communicate about the world, we may begin to better understand how to communicate across languages and cultures, in ways beyond simple translation, that allow us to understand the various nuances of different languages and cultures. All new research shows us that the languages we speak not only reflect or express our thoughts, but also shape the very thoughts we wish to express. The structures that exist in our languages profoundly shape how we construct reality, and help make us as smart and sophisticated as we are.